Efeito do jejum intermitente na saúde óssea em camundongos com obesidade - Bruna Caroline de Oliveira (2024)
Bone tissue performs essential functions such as mechanical support, locomotion, protection and storage of minerals and fat and is closely linked to metabolism and hormonal regulation. Obesity, characterized by excess adipose tissue and chronic low-grade inflammation, can negatively influence bone health by increasing bone fragility due to inflammatory responses and reduced osteoblast formation. Intermittent fasting has emerged as a potential strategy for reducing body fat and improving metabolic health, but its effects on bone health are still scarce and controversial. Therefore, this study aimed to investigate the effect of intermittent fasting as a therapeutic strategy for bone health in mice with obesity. For this, C57BL/6 mice were divided into three experimental groups: (i) mice fed a standard laboratory diet (LABINA®) (C); (ii) mice fed at 45% high-fat diet (HF); and (iii) mice fed an HF diet and subjected to intermittent fasting (IF). The intervention with intermittent fasting was started after the animals in group (iii) reached 40 g, and consisted of 35 days of experimental treatment, interspersing 24 hours of fasting with 24 hours in a state fed with the HF diet. The intervention with intermittent fasting did not reverse the changes in the bone microarchitecture of the femur of obese mice, although it increased the presence of osteoblasts. Intermittent fasting did not affect systemic markers of bone remodeling, nor did it alter the expression of genes related to bone remodeling and maintenance in the tibia. Despite weight reduction, mice subjected to intermittent fasting showed only a partial reversal of adiposity, without significant improvements in the metabolic changes associated with obesity. Thus, intermittent fasting does not appear to have substantial impacts on bone and metabolic health in obese mice.